Solution of the Problem of Empty Car Distribution between Stations and Planning of Way-Freight Train Route Using Genetic Algorithms - Prokhorov, Viktor; Kalashnikova, Tetiana; Rybalchenko, Liliia; Riabushka, Yuliia; Chekhunov, Denys (International Journal of Engineering and Technology, 2018)
In this paper we consider the problem of distributing empty freight cars in a railway polygon. We show how the process can be improved using an optimization model. The optimization model can be characterized as a combination of minimum-cost flow problem with vehicle routing problem. In general, problem of empty railroad car distribution between stations and definition of way-freight train route is presented as integer combinatorial optimization problem. Computational tests show that the model can be solved in acceptable time for real size problems, and indicate that the model generates distribution plans that can improve the quality of the planning process.Â